EKSPLORASI METODE PENELITIAN ETNOGRAFI DALAM MEMAHAMI TRADISI KEAGAMAAN DI SEKOLAH ISLAM - Renal Sipangidoan Siregar; Sulhani Sulhani; Desy Eka Citra Dewi (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
Ethnographic research is a very relevant approach to explore and understand local culture in depth, especially in the context of religious traditions in Islamic schools. By utilizing this method, researchers can explore the values, customs, traditions, and social practices that shape the identity of religious communities in Islamic schools. This article aims to examine the use of ethnographic research methods in studying cultural traditions in Islamic schools, identify the advantages and challenges faced, and provide recommendations for researchers interested in using this approach.